Proposta de um sistema computacional utilizando metáforas aderentes à escrita e leitura musical por deficientes visuais e seus acompanhantes, utilizando células hexadecimais com quatro pontos em relevo, conceitos da numerofonia e a codificação numérica do Código Braille - Lima, Sandra Fernandes de Oliveira (2013)
Learning music, mostly through musical scores, is a difficult task, even for people who do not have visual problems. Learning musical demands years of effort and dedication. Moreover, the music learning tasks for a blind is much more complex. Besides the complexity of the Braille code for music (musicografia Braille), there are few people trained to teach music by this method. This work presents a solution that seeks to simplify the coding of both writing and reading music through cells of raised dots, as also make teaching and learning more attractive, requiring visually impaired and their assistants, less effort, less time and less dedication. This work presents a computational solution that seeks to give the visually impaired, accessibility to the songs as they are posted on the same internet. Unfortunately, the biggest barrier to be faced, it is still a lack of professionals to teach the blind to read such encoding. The proposed system, prototyped and now presents a new simplified coding, presenting the music score in basic cells of 4 points in relief (4 raised dots arranged in cells), musical, textual and Numerofonia format. The proposed method is based on the paradigm of decimal encoding proposed by Braille and the paradigm number already used in international encoding of musical events. The method of this research presents a paradigm that allows, with less effort and less dedication, training of teachers, family members and assistants of visually impaired in learning musical notation proposed here. Learning to read music is relevant due to the fact that, since the assistant learn the paradigm and he can read music, it will be easier to teach visually impaired under his tutelage, the new musicografia. Software was designed and implemented in functional language for generating the codes of this work, as well as other paradigms focused on use by accompanying of visually impaired.